Between Meaning and Benefit: Existentialism and Pragmatism in Viewing Human Life - Haritsahrizal, Muhammad Zaid; Rosy, Marshanda; Parhan, Muhamad; Anugrah, Eri; Ulum, Muhammad Bahrul; Pratama, Gamma Cipta Surya (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
This article aims to analyze existentialism and pragmatism as two schools of philosophy that have been influential in providing views on the meaning and benefits of life for humans. Existentialism and pragmatism are taken as the focus because they offer different approaches to understanding life—existentialism emphasizes individual freedom in creating the meaning of life, while pragmatism places more emphasis on the practical usefulness of ideas and actions. The research method used is content analysis, which involves studying the works of major philosophers from both schools, such as Jean-Paul Sartre, Martin Heidegger, William James, and John Dewey. Data were obtained from various classical philosophical texts as well as articles and books that discuss the practical application of both philosophies in everyday life. The results of the study show that existentialism provides a deep understanding of freedom, responsibility, and the meaning of life that comes from within the individual, while pragmatism offers a view that is more oriented towards the real benefits of actions and ideas, by assessing values based on the practical results produced. This study concludes that although these two schools have different approaches, they complement each other in helping modern individuals find a balance between the search for deep meaning and the need for beneficial outcomes, thus providing a more holistic and relevant perspective in living human life in today's complex era.